Photoshop: Texturing and Shading Techniques. - Bird, Rayce (linkedin.com, 2017)
Learn how to work with shaders, brushes, colors, and highlights in Photoshop to perform shading and texturing of various materials and surfaces—hard, translucent, 3D, and more.